2018
DOI: 10.1111/sode.12324
|View full text |Cite
|
Sign up to set email alerts
|

Between‐ and within‐person predictors of children’s information management following rule violations

Abstract: The purpose of this study was to better understand both why some children disclose more about their misbehavior to their parents than do other children, as well as why a child discloses to parents about misbehavior in some situations but not in others. Analyses test parental warmth, children's beliefs regarding the legitimacy of parental authority and their own obligation to disclose misbehavior, and parent's responses to children's disclosure of disagreement with parents’ rules and children's misbehavior as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Parents struggle to monitor their children's digital activities [33], often leading them to be unaware of online behaviors [1,74]. Although, to our knowledge, no study has explored the predictors of adolescents' self-disclosure of their online behaviors with parents, some related studies [51,75,76,77,78,79,80,81] suggest that authoritative parenting and adolescents' perception of the appropriateness of parenting are associate with adolescents' self-disclosure of o ine behaviors as well [76, 77,80].…”
Section: Mediation Thought Adolescent Self-disclosurementioning
confidence: 99%
“…Parents struggle to monitor their children's digital activities [33], often leading them to be unaware of online behaviors [1,74]. Although, to our knowledge, no study has explored the predictors of adolescents' self-disclosure of their online behaviors with parents, some related studies [51,75,76,77,78,79,80,81] suggest that authoritative parenting and adolescents' perception of the appropriateness of parenting are associate with adolescents' self-disclosure of o ine behaviors as well [76, 77,80].…”
Section: Mediation Thought Adolescent Self-disclosurementioning
confidence: 99%
“…The potential divergence of between-family and within-family processes, referred to as Simpson’s Paradox when the processes are opposite in direction (Kievit, Frankenhuis, Waldorp, & Borsboom, 2013), has received renewed attention within parenting and family process research (Dietvorst et al, 2018; Keijsers, 2016; Keijsers et al, 2016; Laird & Zeringue, 2019; Rekker, Keijsers, Branje, Koot, & Meeus, 2017). Using random intercept cross-lagged panel models (RI-CLPM), Keijsers and colleagues demonstrated that disclosure and delinquency are negatively correlated at the between- but not the within-person level (Keijsers, 2016) and that privacy invasion and secrecy are positively related at the between-person level but negatively related at the within-person level (Dietvorst et al, 2018).…”
Section: Between-family Versus Within-family Processesmentioning
confidence: 99%